Archipelago Proverbs: Building the Prophetic Leadership in Indonesia - Yosi Wulandari, Fitri Merawati, Wachid Eko Purwanto,M. Ardi Kurniawan (International Journal of Advanced Science and Technology, 2020)
This paper aims to describe the following three things. (1) Humanization in the proverbs of the archipelago to build prophetic ethical leadership in Indonesia; (2) liberation in archipelago proverbs to build prophetic ethical leadership in Indonesia and (3) transcendence in archipelago proverbs to build prophetic ethical leadership in Indonesia. The theory used is Kuntowijoyo’s prophetic ethics. This type of research is descriptive qualitative. The results of the study showed that humanitarian prophetic ethics were found in eight proverbs, liberation ethics in fourteen proverbs, and transcendence ethics found in seven proverbs. However, when seen in general, the three ethics are found in all proverbs in the archipelago. Besides, prophetic ethics contained in proverbs has described some of the teachings, advice, or advice to become a prophetic ethical leader in Indonesia. The prophetic ethics contains four examples of Islamic leadership namely shiddiq, amanah, fathonah, and tabligh.